Asymmetric solid burst correcting integer codes - Pankaj Kumar Das; Nabin Kumar Pokhrel (Kuwait Journal of Science)
With the development of technology, communication channels are increasingly experiencing burst faults of various forms caused by noise elements. To get around this, an appropriate encoding and decoding mechanism should be designed while taking into account things like redundancy, memory usage, efficiency, etc. Motivated by these facts, in this paper, we present a class of integer codes capable of correct asymmetric solid burst errors. In addition to the theoretical foundations, the paper also derives the expressions for the probabilities of incorrect and correct decoding for the proposed codes. Lastly, we compare the proposed codes with other similar codes in terms of code rate and memory consumption.